It's on the way: don't give up on your dreams and prayers - Comes, Lisa Osteen (Faith Words, 2021)
Introduction: Don't give up -- Your answer is on the way! -- Let God fight your battles -- When you don't know what to do -- Do it right--no more shortcuts -- Press through until you break through -- Keep calm and shake it off! -- Don't panic--this is just a test! -- What trusting God looks like -- God is planning a resurrection -- Hold on to your seed -- Be joyful now -- Get your fight back.